FORMULASI SEDIAAN HAND BODY GEL DENGAN SARI BUAH RAMBUTAN (Nephelium lappaceum L.) - Nailan Azizah; Nerly Juli Pranita Simanjuntak; Roy Indrianto Bangar (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Rambutan fruit (Nephelium lappaceum L.) contains vitamins A, B, and C, which act as antioxidants and are beneficial for skin health. The utilization of rambutan fruit juice in a hand body gel formulation aims to produce a natural moisturizing product that is safe for use. This study was conducted experimentally by formulating rambutan fruit juice into hand body gel at concentrations of 3%, 5%, and 7%, along with a blank formulation. Each formulation was evaluated for its physical properties, including organoleptic characteristics, homogeneity, pH, spreadability, and viscosity. In addition, skin irritation testing and skin moisture testing using a skin analyzer were performed over three weeks of use. The results showed that all formulations had good physical quality, pH values suitable for the skin, and did not cause irritation. Skin moisture testing indicated an increase in skin moisture in all formulations, with the 7% concentration showing the highest improvement. In conclusion, rambutan fruit juice can be formulated into a hand body gel that is safe and effective as a skin moisturizer, with the 7% concentration being the best formulation.